Militarism and Authoritarian Rule: Visualising Desire for Social and Political Change in The Philippines and Indonesia through The Comics of Nonoy Marcelo and Sapto Raharjo (Athonk) - Dakila A. Fernando, (Wacana Seni Journal of Arts Discourse, 2012)
This article looks into the use of comics as a means to visualise desire for social and political change in societies under authoritarian rule and militarism. Specifically, this study will focus on Bad Times Stories 1 and 2, created by the artist Athonk during the New Order of Indonesian President Suharto, and Ikabod Bubwit, produced by Nonoy Marcelo in the New Society of Philippine President Ferdinand Marcos. Let it be pointed out that the works chosen in this study are symbolic in nature and presuppose an indirect attack on the state. The comics here are witty, humorous, reflective of the pop culture of the time and set in a simulacra world of constant battle between good and evil.